Relasi Pertunjukan Tradisi Barong (Bali) dan Estetika Teater Kekejaman (Antonin Artaud) - Purwanto Lephen (Dance and Theatre Review, 2024)
Reassessment of research results related to Barong performances as a tourist attraction from Bali as a form of differentiation from the sacred Calonarang theater related to Artaud's theater theory. Barong's presentation at the Paris International Colonial Exposition (1931) was appreciated and inspired the renewal of theater aesthetics from conventional (psychological and dramatic logic) to non-conventional (nonverbal and symbolic) theater. Criticism of Artaud's opinion regarding theater (for tourist attractions) Barong Ubud Bali is considered inappropriate and has not understood the art and culture of Balinese tradition. This research was conducted by reviewing the Barong performance form with the aesthetic theory of cruelty theater (Artaud). Qualitative research method by describing the Barong performance and complemented by literature review. The results showed that Artaud's theory of theater aesthetics is different and cannot be applied to study the aesthetics of Barong traditional theater which analyzes theatrical elements, scenes, actor expressions, music, gestures, clothing, masks, and properties with metaphysical concepts, natural chaos, or terror theater. So Artaud's theater of terror updates the form of modern (French) theater, not the result of reformulation and conception of Barong theater performances.